Justice or compassion? Cultural differences in power norms affect consumer satisfaction with power-holders. Issue 3 (11th May 2015) - Torelli, Carlos J.; Shavitt, Sharon; Cho, Young Ik; Holbrook, Allyson L.; Johnson, Timothy P.; Weiner, Saul
Abstract : Purpose: – The purpose of this paper is to investigate cultural variations in the qualities that White Americans and Hispanic Americans believe power-holders should embody, and the situations in which these norms influence consumer satisfaction. Design/methodology/approach: – Two experimental studies ( n 1=130 and n 2=121) and one field study ( n =241) were conducted with White American and Hispanic participants. Results were analysed using ANOVA and regression. Findings: – White Americans are predisposed to apply to power-holders injunctive norms of treating others justly and equitably, whereas Hispanics are predisposed to apply injunctive norms of treating others compassionately. These cultural variations in the use of injunctive norms were more evident in business or service contexts in which power was made salient, and emerged in the norms more likely to be endorsed by White American and Hispanic participants (Study 1), their approval of hypothetical negotiators who treated suppliers equitably or compassionately (Study 2), and their evaluations of powerful service providers in a real-life, on-going and consequential interaction (Study 3). Research limitations/implications: – This research suggests key implications for our theoretical understanding of the role of social norms in carrying cultural patterns, as well as for cross-cultural theories of consumer satisfaction with service providers. Practical implications: – Marketers should pay attention to signals of fairness (compassion) in their services, as perceptions of fairness (compassion) by White American (Hispanic) consumers can boost satisfaction ratings. This is particularly important in service encounters that might be characterized by power differentials, such as those in health care and financial services. Originality/value: – As consumer markets grow more culturally diverse, it is important for marketers to understand how distinct notions of power impact the attitudes and behaviors of consumers from different cultures. This research investigates the implications of distinct power concepts for multi-cultural consumers' evaluations of service providers, an important and under-researched area with implications for global service management.